The Effect of Innovation Capability on Market Performance Mediated by External Collaboration on SMEs - Trio Febriyantoro, Mohamad; ., Zulkifli; Totok Suyoto, Yohanes; Saputra, Fendi; Suleman, Dede (KnE Social Sciences, 2023)
The functions and roles of SMEs in Indonesia are quite numerous both economically, politically, socially, culturally, and securely. Economic-social-political functions and roles, for example, are to increase people’s income, reduce unemployment, poverty, and urbanization flows. This study aims to determine the effect of innovation capability on market performance mediated by external collaboration in Batam SMEs. This study took a sample of 257 respondents, who are managers or owners of SMEs, selected using non-probability sampling method with purposive sampling technique. Data were analyzed using structural equation modeling with partial least square (SEM PLS) approach. The results showed that innovation capability has a significant effect on market performance in SMEs, a significant relationship was observed between innovation capability and external collaboration and between external collaboration on market performance, while the results of the indirect effect showed that external collaboration mediates the relationship between innovation capability and market performance. Suggestions for Batam City SMEs to continue to maximize innovation capabilities and collaborate with various parties to improve market performance. Keywords: innovation capability, market performance, external collaboration, MSMEs